Feasibility study of hybrid propulsion systems for long-liner fishing vessels - Andersson, Alexander; Logason, Kári (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2015)
Fluctuating and unpredictable fuel prices in combination with new environmental regulations and increased awareness of shipping impact on global greenhouse gas emissions have brought the interest of ship owners into investigating further alternative propulsion and power plant systems for increased efficiency and reduction of emissions. In recent years there has been a growing interest in the shipping industry to apply hybrid propulsion system including batteries. Fishing and its related activities constitute a significant part of the shipping business, in particular in some countries such as Iceland and Norway. In the past most designs have been performed with focus on the so called design condition for vessels. However, both due to the fishing method and environmental conditions, the vessels are operating in a number of different conditions from what was assumed in the original design process. In this thesis, the operational pattern is investigated for an existing long-liner fishing vessel in the Icelandic fleet, based on an empirical approach along with on board measurements. The current propulsion and power plant of the long-liner fishing vessel under consideration is compared with alternative designs including hybrid and diesel-electric propulsion in terms of efficiency and bunker consumption. The comparisons are obtained by simulation models of the propulsion systems and use the estimation and measurement of the power requirement as an input data. Finally, an economical comparison based on estimations of the additional costs for the proposed design alternatives is presented. When trends on market, the operational pattern and the economical evaluation are summarized, it indicates future potential for hybrid propulsion for long-liner fishing vessels.